2008
DOI: 10.1002/jez.452
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic and conservation genetic analysis of the black caiman (Melanosuchus niger)

Abstract: We assessed the spatial distribution of the genetic variability of Melanosuchus niger from 11 localities in South America using 1,027 base pairs of the mitochondrial cytochrome b gene. Screening 132 animals, we found 41 haplotypes, high values of genetic diversity, low values of nucleotide diversity and significant deviations from neutral expectation of allelic frequencies in some localities. Mantel test and nested-clade analysis indicated that isolation-by-distance was an important population dynamic for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…The Amazon basin lineage is structured along an east–west gradient, with a sharp transition in haplotype group frequencies to the east and west of the Negro and Madeira rivers. This pattern is also observed in other groups of reptiles (e.g., Glor, Vitt & Larson, 2001 ; Kronauer et al, 2005 ; Gamble et al, 2008 ), amphibians ( Simula, Schulte & Summers, 2003 ), and caimans ( Vasconcelos et al, 2006 ; Vasconcelos et al, 2008 ). Vasconcelos et al (2006) found significant genetic structure between Caiman crocodilus sampled in localities of the Amazon basin and Atlantic coast drainages paralleling the pattern found in P. trigonatus .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The Amazon basin lineage is structured along an east–west gradient, with a sharp transition in haplotype group frequencies to the east and west of the Negro and Madeira rivers. This pattern is also observed in other groups of reptiles (e.g., Glor, Vitt & Larson, 2001 ; Kronauer et al, 2005 ; Gamble et al, 2008 ), amphibians ( Simula, Schulte & Summers, 2003 ), and caimans ( Vasconcelos et al, 2006 ; Vasconcelos et al, 2008 ). Vasconcelos et al (2006) found significant genetic structure between Caiman crocodilus sampled in localities of the Amazon basin and Atlantic coast drainages paralleling the pattern found in P. trigonatus .…”
Section: Discussionsupporting
confidence: 72%
“… Vasconcelos et al (2006) found significant genetic structure between Caiman crocodilus sampled in localities of the Amazon basin and Atlantic coast drainages paralleling the pattern found in P. trigonatus . While isolation-by-distance was discarded by the authors for C. crocodilus , it appears to have been an important structuring factor for Melanosuchus niger populations sampled across the Amazon basin and Atlantic coast drainages ( Vasconcelos et al, 2008 ) paralleling the east–west divergence observed in P. trigonatus .…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to that seen in extant crocodylian subdivisions of West African ecosystems; the species Crocodylus suchus (West African Crocodile), Mecistops cataphractus (West African slender-snouted crocodile) and Osteolaemus tetraspis (African Dwarf Crocodile) do not inhabit similar bodies of water (Kofron, 1992;Velo-Antón et al, 2014), and with decreasing size, all species live in smaller waterways, with Osteolaemus being capable of terrestrial foraging. This could be similar to the hierarchy seen in South American caimans: Melanosuchus niger (Black Caiman), Paleosuchus palpebrosus (Cuvier's Dwarf Caiman), Caiman yacare (Yacare Caiman), Caiman crocodilus (Spectacled Caiman) and Caiman latirostris (Broad-Snouted Caiman) (Ross, 1998;Busack & Pandya, 2001;Rebêlo & Lugli, 2001;Vasconcelos et al, 2008).…”
Section: Taxamentioning
confidence: 54%
“…; and reptiles: Vasconcelos et al . , ). These data indicate that the population structure may be an outcome of barriers that are no longer evident in the landscape (ancient rivers) (Lougheed et al .…”
Section: Resultsmentioning
confidence: 99%